Vanuatu : 2013 Article IV Consultation. (Washington, D.C. : International Monetary Fund, 2013)
Vanuatu has a comparatively favorable economy and cautious macroeconomic policies that have helped maintain stability and confidence. Financial sector policies also have been appropriately cautious. The economy must maintain low debt in the longer term, but as funding is needed for infrastructure, maintenance, and social services, new revenue measures have to be identified. This revenue could help strengthen the state while maintaining growth potential, especially in the tourism and agricultural sectors. The financing options for new large infrastructure projects have to be assessed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet